Determinants of Job Satisfaction - Mandasari Pohan, Indri; Farida Ferine, Kiki (PT. Multidisciplinary Press Indonesia, 2024)
This research aims to examine the influence of compensation and organizational climate on job satisfaction in moderating organizational commitment at the Bank Indonesia Representative Office in North Sumatra Province. Human Resource Management (HRM) is an important factor and the heart of every business. This is caused by the vigilant attitude of the human resources management team towards the workforce of each employee in the company. The results of this research are as follows: Compensation has a negative and insignificant effect on Job Satisfaction and is moderated by organizational commitment with a value of -0.019 and a value of 0.455. Organizational climate has a negative and insignificant effect on job satisfaction and is moderated by organizational commitment with a value of -0.074 and a value of 0.296. Organizational climate has a positive and significant effect on job satisfaction with a value of 0.273 and a value of 0.045. Organizational Commitment has a positive and significant effect on Job Satisfaction with an original sample value of 0.496 and ap value of 0.000. Compensation has a positive and significant effect on Job Satisfaction with an original sample value of 0.215 and ap value of 0.006.